Implementasi Kurikulum Merdeka dalam Menumbuhkan Kemampuan Critical Thinking di Kelas XI F1 pada Mata Pelajaran Pendidikan Agama Islam di SMAN 8 Padang - Ravid, Muhammad; Sulaiman, Sulaiman (ISLAMIKA, 2024)
This study aims to describe: 1) the planning of implementing the Merdeka Curriculum in fostering critical thinking skills in Class XI F1 for Islamic Religious Education subjects; 2) the implementation of the Merdeka Curriculum in developing critical thinking skills in Class XI F1 for Islamic Religious Education subjects; 3) the challenges and efforts faced by Islamic Religious Education teachers in nurturing critical thinking in Class XI F1 for Islamic Religious Education subjects. The research method used is qualitative with a descriptive approach. The results of the study show that, first, in the planning stage, teachers attended training, prepared teaching modules that included learning objectives, teaching models, learning activities, and assessment/evaluation. Second, the implementation involved preparatory activities such as preparing media/tools and motivating students in line with the Pancasila Student Profile. The core activities included activities 1.1, 1.2, and 1.3, while closing activities consisted of summarizing the lesson, reflecting, providing information about future learning, and concluding with a prayer. Third, the challenges faced by teachers included inadequate training and continued use of lecture-based methods. The efforts made to address these challenges included attending further training and mastering various teaching models.